2015
DOI: 10.3389/fnins.2015.00395
|View full text |Cite
|
Sign up to set email alerts
|

ICA-based artifact removal diminishes scan site differences in multi-center resting-state fMRI

Abstract: Resting-state fMRI (R-fMRI) has shown considerable promise in providing potential biomarkers for diagnosis, prognosis and drug response across a range of diseases. Incorporating R-fMRI into multi-center studies is becoming increasingly popular, imposing technical challenges on data acquisition and analysis, as fMRI data is particularly sensitive to structured noise resulting from hardware, software, and environmental differences. Here, we investigated whether a novel clean up tool for structured noise was capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 50 publications
(83 reference statements)
1
41
0
Order By: Relevance
“…These additional sources of unwanted variability may decrease statistical power and lead to spurious results. Many multi-site studies have reported considerable site or scanner effects in fMRI data (Friedman et al, 2006, 2008; Suckling et al, 2008, 2010; Van Horn and Toga, 2009; Gountouna et al, 2010; Brown et al, 2011; McGonigle, 2012; Turner et al, 2013; Forsyth et al, 2014; Feis et al, 2015; Rath et al, 2016; Jovicich et al, 2016; Dansereau et al, 2017; Noble et al, 2017; Abraham et al, 2017). However, most of these studies only describe the problem or report the magnitude of site effects in fMRI measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These additional sources of unwanted variability may decrease statistical power and lead to spurious results. Many multi-site studies have reported considerable site or scanner effects in fMRI data (Friedman et al, 2006, 2008; Suckling et al, 2008, 2010; Van Horn and Toga, 2009; Gountouna et al, 2010; Brown et al, 2011; McGonigle, 2012; Turner et al, 2013; Forsyth et al, 2014; Feis et al, 2015; Rath et al, 2016; Jovicich et al, 2016; Dansereau et al, 2017; Noble et al, 2017; Abraham et al, 2017). However, most of these studies only describe the problem or report the magnitude of site effects in fMRI measurements.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, until now, there has been only one attempt to diminish scanner differences in multi-site resting-state fMRI post-acquisition. The authors used an independent component analysis (ICA) based approach that reduced differences across sites in some resting-state network connectivity measures but did not fully eliminate the structured noise arising from different scanners (Feis et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…While straightforward to implement in single-subject analyses, group ICA analyses are more complex and require choosing between several different workflows and algorithm definitions (Beckmann and Smith, 2004; Calhoun et al, 2009; Schöpf et al, 2010; Du et al, 2016). ICA methods also have been used extensively in rs-fMRI studies (Beckmann et al, 2005; Soares et al, 2016), task-based fMRI (Calhoun et al, 2008), and for artifact removal (Perlbarg et al, 2007; Feis et al, 2015; Pruim et al, 2015). …”
Section: Analysis Methodsmentioning
confidence: 99%
“…The purpose of data preprocessing is to obtain the data set of segmented EEG signals, including the removal of EOG (Electro-Oculogram) [33][34][35][36], epoch, filtering, etc. In this paper, data preprocessing is realized using Scan 4.3 software (Neuroscan).…”
Section: Data Preprocessingmentioning
confidence: 99%